(untitled) (JS (JURNAL SEKOLAH), 2025)
Abstract: This study was conducted with the aim of designing and developing a Pop-Up Book as a learning medium on the topic of ecosystems to improve the learning outcomes of fifth-grade elementary school students. The research approach used was Research and Development (R&D), applying the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The instruments employed in this study included expert validation questionnaires as well as pre-test and post-test assessments, analyzed using descriptive quantitative methods. Based on the validation results, the media was deemed highly appropriate for use in learning, with feasibility scores of 84% from the material expert, 90% from the media expert, and 98% from the education practitioner. The average student score increased from 56% before the learning process to 87% afterward. These findings indicate that the Pop-Up Book is an effective and suitable learning medium for science education in elementary schools. Keyword: Learning Outcomes, Pop-Up Book, science education Abstrak: Penelitian ini dilakukan dengan tujuan untuk merancang dan mengembangkan media pembelajaran berbentuk Pop-Up Book pada topik ekosistem guna meningkatkan hasil belajar siswa kelas V sekolah dasar. Pendekatan penelitian yang digunakan adalah Research and Development (R&D) dengan menerapkan model pengembangan ADDIE, yang mencakup tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Instrumen yang digunakan dalam penelitian ini meliputi angket validasi dari para ahli serta tes pre-test dan post-test, yang dianalisis menggunakan metode deskriptif kuantitatif. Berdasarkan hasil validasi, media dinyatakan sangat layak digunakan dalam pembelajaran, dengan skor kelayakan dari ahli materi sebesar 84%, ahli media 90%, dan praktisi pendidikan 98%. Rata-rata nilai siswa meningkat dari 56% sebelum pembelajaran menjadi 87% setelah pembelajaran berlangsung. Temuan ini menunjukkan bahwa media Pop-Up Book efektif dan sesuai untuk diterapkan dalam pembelajaran IPA di sekolah dasar. Kata Kunci: Hasil Belajar, Pop-Up Book, Pendidikan IPA